Effects of auditory information on self-motion perception during simultaneous presentation of visual shearing motion - Tanahashi, Shigehito; Ashihara, Kaoru; Ujike, Hiroyasu (Frontiers in Psychology, 2015)
Recent studies have found that self-motion perception induced by simultaneous presentation of visual and auditory motion is facilitated when the directions of visual and auditory motion stimuli are identical. They did not, however, examine possible contributions of auditory motion information for determining direction of self-motion perception. To examine this, a visual stimulus projected on a hemisphere screen and an auditory stimulus presented through headphones were presented separately or simultaneously, depending on experimental conditions. The participant continuously indicated the direction and strength of self-motion during the 130-s experimental trial. When the visual stimulus with a horizontal shearing rotation and the auditory stimulus with a horizontal one-directional rotation were presented simultaneously, the duration and strength of self-motion perceived in the opposite direction of the auditory rotation stimulus were significantly longer and stronger than those perceived in the same direction of the auditory rotation stimulus. However, the auditory stimulus alone could not sufficiently induce self-motion perception, and if it did, its direction was not consistent within each experimental trial. We concluded that auditory motion information can determine perceived direction of self-motion during simultaneous presentation of visual and auditory motion information, at least when visual stimuli moved in opposing directions (around the yaw-axis). We speculate that the contribution of auditory information depends on the plausibility and information balance of visual and auditory information.